ANALYSIS OF THE CHARACTER VALUES OF THE MAIN CHARACTERS IN THE NOVEL 'RE DAN PEREMPUAN' BY MAMAN SUHERMAN AND ITS UTILIZATION AS TEACHING MATERIAL FOR NOVEL STUDIES - Nurlaelah, Ela; Efendi, Irfan; Naufal, Muji Zain (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2023)
Literary works are an experience that can be learned from and provide lessons for reflection to readers. The novel is a type of fictional literary work that cannot be missed, which is currently developing rapidly in Indonesia. The method used in this research is a qualitative descriptive research method. This research will analyze the character values found in the main characters in the novel Re: dan peREmpuan by Maman Suherman. This research is very interesting because through studying literature, new learning and thinking can be gained. Researchers found 74 data showing the character values of the main characters in the novel Re: dan peREmpuan by Maman Suherman. The eighteenth character values according to the Ministry of Education and Culture in the main character Rere by Maman Suherman, first religious, found 5 quotes, second curiosity found 6 quotes, third honest, found 6 quotes, fourth independent found 2 quotes, fifth friendly found 5 quotes, sixth caring environment found 2 quotes, seventh tolerance found 4 quotes, eighth discipline found 3 quotes, ninth creative thinking found 4 quotes, tenth responsibility found 6 quotes, eleventh social care found 3 quotes, twelfth democratic found 5 quotes, thirteenth hard work found 4 quotes, the fourteenth found 4 quotes about national spirit, the fifteenth likes reading 3 quotes were found, the sixteenth appreciated achievements found 4 quotes, the seventeenth love of the homeland found 3 quotes and the eighteenth love of peace found 5 quotes in the novel.